2003
DOI: 10.2307/3078881
|View full text |Cite
|
Sign up to set email alerts
|

Does Herbivore Diversity Depend on Plant Diversity? The Case of California Butterflies

Abstract: It is widely believed that the diversity of plants influences the diversity of animals, and this should be particularly true of herbivores. We examine this supposition at a moderate spatial extent by comparing the richness patterns of the 217 butterfly species resident in California to those of plants, including all 5,902 vascular plant species and the 552 species known to be fed on by caterpillars. We also examine the relationships between plant/butterfly richness and 20 environmental variables. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 0 publications
6
93
2
Order By: Relevance
“…Haddad et al (2001) and Siemann et al (1998) found positive correlations between species richness of terrestrial plants and insects in experimental grasslands on scales of 10 m 2 . Hawkins and Porter (2003) found positive correlations between butterfly and plant diversity between bioregions in California, USA, although the relationship disappeared after accounting for variation due to productivity and topographic gradients. Their study suggested that correlations in diversity across trophic levels were driven by a correlated response to the environment rather than by direct causal links.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Haddad et al (2001) and Siemann et al (1998) found positive correlations between species richness of terrestrial plants and insects in experimental grasslands on scales of 10 m 2 . Hawkins and Porter (2003) found positive correlations between butterfly and plant diversity between bioregions in California, USA, although the relationship disappeared after accounting for variation due to productivity and topographic gradients. Their study suggested that correlations in diversity across trophic levels were driven by a correlated response to the environment rather than by direct causal links.…”
Section: Discussionmentioning
confidence: 98%
“…That is, high diversity of producers should coincide with high diversity among consumers and decomposers. Most studies of diversity patterns across trophic levels come from terrestrial systems and largely focus on primary producer and herbivore interactions (Murdoch et al 1972, Siemann et al 1998, Haddad et al 2001, Hawkins and Porter 2003. Most terrestrial studies have found positive correlations in diversity across trophic groups.…”
Section: Introductionmentioning
confidence: 99%
“…While cross-taxon associations in richness patterns above and beyond environment are found (27), environmental variables such as temperature and productivity tend to be much stronger predictors and surrogates (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Observations in South America and elsewhere show strong positive linkage between plant and insect-herbivore diversity (8)(9)(10)(11)(12)(13)(14). Proposed mechanisms include dependency of insect diversity on plant diversity (8, 9, 13), coevolution of plants and insects (15-21), herbivore selection against host density (22-25), and herbivore intensification of abiotic factors that select for habitat specialization (26,27).…”
mentioning
confidence: 99%